Wujud Allah, Ilmu Allah dan Ma’iyatullah - Wahyuddin (Universitas Islam Negeri Alauddin Makassar, 2024)
Wujud is the first of the twenty attributes god ought to be. We believe in god almighty. It exists. Surely god is with his dz(god himself) not through any mediator. And what a obligatory form god is, it cannot be accompanied by nothing. God's form almighty. It wasn't through any medium. It wasn't created by anyone. Because if it is manifest through the medium, then god almighty. It will be just like it needs an intermediary to realize. God almighty. Not like his creatures. The existence of god is the dsubstance of god itself. God is something we must believe in. The meaning of the word duty itself is that when there is not a single image in the sense of the word it is there must be a god. Not impossible and not possible. God is not presented. it does not exist. Unlike its creatures or creations that existed after the beginning. Like a man born of his mother's belly. That man now exists after being born that never existed. Whereas god almighty. He didn't look like that. Proof of god's godship. Is this whole natural thing. How could this universe exist if no one created it? How can this world and all of it function so well when nothing isin control? Then the existence of this whole realm, this world, is proof of god. It exists. There is. No one knows the form of god. Also, there is no Koratn or prophetic explanation of this. The explanation is that god cannot be imagined by human imagination. Therefore, thinking of god's form can only stress us because our logic will not lead to anything. Furthermore, it can potentially depreciate in faith because human nature is prone to depression when in a confused, rational condition, unable to suppress the urge for curiosity. Therefore, god recommends that to know the existence of god, we should simply pay attention to his creatures in order to increase our confidence in god's existence and increase our confidence in him to do his commandments and to walk away from them and that all that god has stated in the Koran is true.